A Look the Halal Fashion Industry in Indonesia and the Struggles It Faces on a Global Scale - Masuwd, Mowafg Abrahem (Danadyaksa: Post Modern Economy Journal, 2024)
The global Muslim population is widely dispersed, with Indonesia having the largest Muslim majority. The halal industry, including the modest fashion sector, operates within an increasingly competitive global market. This study examines the development and challenges of Indonesia’s modest fashion industry within the global halal economy, addressing the critical barriers to its international expansion. Utilizing a qualitative research design with a descriptive approach, this study analyzes data from industry reports, policy documents, and relevant literature. The findings indicate that Indonesia’s Global Islamic Economy Indicator (GIEI) score for the fashion sector improved significantly from 2018 to 2021, positioning the country among the top 10 globally. However, this growth aligns with similar trends observed in competing nations, indicating that Indonesia still faces substantial challenges in maintaining its competitive edge. Key barriers include limited access to financing, difficulties in penetrating international markets, evolving consumer demands, inconsistent government policies, and the need for technological advancements in marketing, research, and development. Despite these obstacles, Indonesia’s modest fashion industry continues to expand, driven by increasing global recognition and ongoing industry innovation. The study highlights the need for strategic policy interventions and enhanced industry collaborations to strengthen Indonesia’s position in the global halal fashion market.